2016
DOI: 10.1097/md.0000000000005308
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the risk of left ventricular free wall rupture in Taiwanese patients with ST-elevation acute myocardial infarction undergoing different reperfusion strategies

Abstract: Ventricular free wall rupture (VFWR) is the second most common cause of death in patients with acute ST-elevation myocardial infarction (STEMI). Nevertheless, few reports have investigated the factors, including different treatment strategies, associated with VFWR in Taiwanese patients. Therefore, the aim of this study was to compare the risk of VFWR in Taiwanese patients with acute STEMI who had received primary percutaneous coronary intervention (PCI), rescue PCI, scheduled PCI, thrombolytic therapy, and pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 30 publications
1
10
0
Order By: Relevance
“…The overall incidence of CR reported in the literature prior to the pPCI era was 10-20% [2], and the incidence of CR reported over the recent 10 years is around 1% [1,13,14]. In the current study, the in-hospital incidence of CR was 1.4% in STEMI patients.…”
Section: Discussionmentioning
confidence: 42%
“…The overall incidence of CR reported in the literature prior to the pPCI era was 10-20% [2], and the incidence of CR reported over the recent 10 years is around 1% [1,13,14]. In the current study, the in-hospital incidence of CR was 1.4% in STEMI patients.…”
Section: Discussionmentioning
confidence: 42%
“…We found that the incidence of both CR and LVT after MI was 1.14% or 1.45%, respectively. The figure was markedly lower in earlier clinical reports of 3–10% for CR ( 8 , 15 ) and 25–40% for LVT ( 10 , 16 , 22 ) but comparable to recent literature ( 8 , 42 , 43 ). We speculate that, under the current management of acute MI, clinical manifestations of CR might have changed in a proportion of patients to the early formation of LVT.…”
Section: Discussionsupporting
confidence: 80%
“…The overall incidence of CR reported in the literature prior to the pPCI era was 10-20% 2 , and the incidence of CR reported over the recent 10 years is around 1% 1,14,15 . In the current study, the in-hospital incidence of CR was 1.4% in STEMI patients.…”
Section: Discussionmentioning
confidence: 99%